Skinner Sweet, American Vampire - James J. Donahue (European Journal of American Studies)
In their series American Vampire, Scott Snyder and Rafael Albuquerque create a new breed of vampire, one specific to America. In the full-length collections of their current series, Snyder and Albuquerque explore issues of American identity through the improbable birth and activities of this new breed and those who encounter it. Reborn as a vampire during the American west of the 1880s, Skinner Sweet embodies an American identity defined by the myth of the west and the American Dream it gave birth to. As an outlaw both in the eyes of the law as well as in the eyes of the older, European clans, Skinner embodies the spirit of revolution against tradition that has become one of the cornerstones of American identity associated with American frontier of rugged individualism. Similarly, as the first vampire born in America (in a space generally acknowledged as the birthplace of the American mythology), the ruthless killer Skinner also embodies the savagery associated with the Native Americans; and, like members of other indigenous tribes, Skinner is hunted by white lawmen for his crimes against civilization. As such, Skinner is both the savage “native” American whose execution is sought by the “civilized” whites, as well as the brash American seeking his Emersonian independence from European tradition. In the subsequent storylines, Skinner Sweet finds himself at various iconic moments of American cultural history: Hollywood in the 1920s, Las Vegas in the 1930s, and the Second World War. By placing Skinner in these moments, Snyder and Albuquerque select a specific timeline by which to chart America’s development.